Breast milk supplementation and preterm infant development after hospital discharge: a randomized clinical trial - Cunha,Roxana Desterro e Silva da (2016)
Abstract Objectives: To assess the effect of maternal breast milk supplementation on the development of exclusively breast-fed very low birth weight preterm infants at 12 months of corrected age. Methods: A randomized clinical trial with 53 infants followed-up after discharge from the neonatal unit until a corrected gestational age of 12 months. Newborns in the intervention group were breastfed exclusively with maternal milk and received 2 g of a multinutrient supplement (Pré-Nan®, Nestlé, Vevey, Switzerland) added to expressed breast milk twice a day until a corrected age of 4–6 months. The control group was exclusively breastfed without supplementation. After monthly follow-up, developmental assessment was performed using the Bayley III Scale. Results: There was no statistically significant difference on the Bayley III Scale between the intervention and control groups in any of the assessed domains: motor, cognitive, and communication. However, scores in the three domains were always higher in the group that received the supplement. There were a similar number of cases of developmental delay in both groups: seven (28%) in the group that received the supplement and nine (33.3%) in the group that was exclusively breastfed. Conclusions: The results failed to show an association between post-discharge multinutrient supplementation and development in the assessed infants.